Elucidation of the absolute configuration of rhizopine by chiral supercritical fluid chromatography and vibrational circular dichroism. Issue 14 (7th July 2015) - Krief, Alain; Dunkle, Melissa; Bahar, Masoud; Bultinck, Patrick; Herrebout, Wouter; Sandra, Pat
<x xml:space="preserve">Abstract</x> The absolute configuration of rhizopine, an opine‐like natural product present in nitrogen‐fixing nodules of alfalfa infected by rhizobia, is elucidated using a combination of state‐of‐the‐art analytical and semi‐preparative supercritical fluid chromatography and vibrational circular dichroism spectroscopy. A synthetic peracetylated racemate was fractionated into its enantiomers and subjected to absolute configuration analysis revealing that natural rhizopine exists as a single enantiomer. The stereochemistry of non‐derivatized natural rhizopine corresponds to (1R, 2S, 3R, 4R, 5S, 6R)‐4‐amino‐6‐methoxycyclohexane‐1, 2, 3, 5‐tetraol.